La descriminación étnica y los estados emocionales de los estudiantes de los octavos años de educación básica paralelos A, B, C, del Colegio Nacional Mixto Simón Bolívar, periodo lectivo 2013-2014. - Ramírez Carriel, Jéssica Jessenia (2014)
This thesis research. Ethnic discrimination and emotional states of students in the eighth year of basic education parallel A, B, C, and C of the Joint National College Simon Bolivar 2013-2014 academic year, is framed in achieving reduce extreme social imbalances and provide its citizens with opportunities for integral development and coexistence based on respect for the law and the exercise of human rights, promoting inclusive development supported its multiethnic and multicultural roots, promoting the application of criteria and measures to prevent and eliminate discrimination in the education system.